Hepatopancreatoduodenectomy for perihilar cholangiocarcinoma following laparoscopic total gastrectomy. (2017) - Chiba, Naokazu; Gunji, Takahiro; Ozawa, Yosuke; Hikita, Kosuke; Sano, Toru; Tomita, Koichi; Abe, Yuta; Kawachi, Shigeyuki
Highlights: Surgical resection is the only curative treatment for perihilar cholangiocarcinoma. Hepatopancreatoduodenectomy for biliary cancers after total gastrectomy is a challenging procedure with high morbidity and mortality rates. However, this procedure can provide the chance for long-term survival if curative resection is feasible. This case was the first report of hepatopancreatoduodenectomy following laparoscopic total gastrectomy. Abstract: Introduction: Surgical resection is the only curative treatment for perihilar cholangiocarcinoma. However, Hepatopancreatoduodenectomy (HPD) procedure remains controversial in regard to the balance between the survival benefit and high risk of mortality and morbidity. Presentation of case: A 72-year-old man who was revealed the dilation of intrahepatic hepatic duct by computed tomography after laparoscopic total gastrectomy was referred to our hospital. The patient had undergone laparoscopic total gastrectomy with Roux-en-Y esophageal-jejunostomy reconstruction 1 year previously. By several examinations, we consequently diagnosed this case as a perihilar cholangiocarcinoma and performed HPD. Histological examination revealed a well differentiated adenocarcinoma without lymph-node metastasis and a negative margin of liver parenchyma and pancreas. He was recovered from a grade B pancreatic fistula by conservative therapy and discharged post-operatively on day 64 in good health. The patient received postoperative systemic chemotherapy with gemcitabine for 6 months. 16 months after surgery, the patient has had no recurrence. Discussion: HPD for biliary and cancers after total gastrectomy is a challenging procedure with high morbidity and mortality rates. However, this procedure can provide the chance for long-term survival if curative resection is feasible. Conclusion: This case was the first report of hepatopancreatoduodenectomy following laparoscopic total gastrectomy.